Compliance Predictors Are Mandatory Vehicle Tax - Ni Kadek Putri HANDAYANI; Ni Nengah Seri Ekayani EKAYANI; Putu Gede Wisnu Permana KAWISANA (Journal of Tourism Economics and Policy, 2021)
The purpose of this study was to determine the predictors of motor vehicle taxpayer compliance. The population in this study were taxpayers registered at the Samsat Bersama Tabanan Office. The number of samples used in this study amounted to 100 respondents calculated based on the Slovin formula with the method of determining the sample accindental sampling and tested using multiple linear regression models with the help of SPSS 24. The data used are primary and secondary data obtained or collected by researchers directly from the data source. To obtain data in this study was carried out through questionnaires distributed to taxpayers at the Samsat Bersama Tabanan Office. The results showed that the variables of Taxpayer Awareness, Tax Sanctions, Tax Knowledge, Service Quality, Tax Socialization and the Drive Thru Samsat System had a positive effect on motor vehicle taxpayer compliance at the Samsat Joint Tabanan Office.